Design Flexural Piezoelectric Acoustic Transducers Array based d33 Mode Polarization - K.A. Ahmad; A. Abd Manaf; Z. Hussain Hussain; Z. Janin (Institute of Advanced Engineering and Science, 2018)
Piezoelectric Acoustic Transducer (PAT) is a transducers used in many application such as medical diagnostic, medical ultrasonic imaging and underwater acoustic applications. Latest research, PAT were investigated in marine application and underwater acoustic imaging. Conventional PAT is design based on sensing element, Piezoelectric Material, matching layer and backing layer. But the conventional method still has problem with issues of narrow bandwidth, directivity and low sensitivity. This problem is occurred when the transducer need to increase the image resolution. The size of single element will become smaller to meet the requirement of high resolution. PZT-5H have high piezoelectric constant (d31) and low dielectric loss. It is chosen as sensing element in this design of PAT because it will increase the sensitivity of transducers. The PAT is design based on d33 mode polarization to improve the receiving sensitivity. The fabrication process are included wet etching on Printed Circuit Board (PCB), spin coated Polydimethylsiloxane (PDMS), and baked transducer on hot plate. PAT is characterized using Pulse-Echo method. Pulse-Echo method will determine the sensitivity, directivity and operating bandwidth of acoustic transducers in underwater applications. Open circuit receiving voltage (OCRV) is voltage response to determine the sensitivity of acoustic transducer. The commercial projector and hydrophone will calibrate to obtain the reliability of result. In cross talk test, at some particular frequency, Pin 2 and Pin 3 have low sensitivity value. It is because Pin 2 and Pin 3 received low acoustic wave pressure. The PAT array based d33 mode polarization shows it has more receiving sensitive compared to commercial acoustic transducers. The design transducer has sensitivity at -56 dB re 1V/µPa at resonance frequency, 100kHz and fractional bandwidth at 30%.